2017
DOI: 10.1002/hyp.11247
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurements of soil saturated hydraulic conductivity: Assessment of reliability through rainfall-runoff experiments

Abstract: The saturated hydraulic conductivity, K s , is a soil property that has a key role in the partitioning of rainfall into surface runoff and infiltration. The commonly used instruments and methods for in situ measurements of K s have frequently provided conflicting results. Comparison of K s estimates obtained by three classical devices-namely, the double ring infiltrometer (DRI), the Guelph version of the constant-head well permeameter (GUELPH-CHP) and the CSIRO version of the tension permeameter (CSIRO-TP) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 54 publications
0
25
0
2
Order By: Relevance
“…The synthesis here indicates that positive head applied as the surface boundary condition has an effect when greater than 0.5 cm, with a power-law relation between K fs and positive (i.e. For example, Morbidelli et al (2017) compared TI, FHP, and SSRS K fs estimates and found that TI and SSRS methods produced similar mean K fs , but TI K fs was more variable, whereas FHP produced K fs estimates that were larger on average by nearly a factor of 5 compared to SSRS. The minimum ponded pressure head used in the datasets reported here was 0.5 cm, so that is the lower limit of ponded head that this analysis can identify but if there is a significant threshold pressure head it may be smaller.…”
Section: Measurement Methods Impactsmentioning
confidence: 76%
See 1 more Smart Citation
“…The synthesis here indicates that positive head applied as the surface boundary condition has an effect when greater than 0.5 cm, with a power-law relation between K fs and positive (i.e. For example, Morbidelli et al (2017) compared TI, FHP, and SSRS K fs estimates and found that TI and SSRS methods produced similar mean K fs , but TI K fs was more variable, whereas FHP produced K fs estimates that were larger on average by nearly a factor of 5 compared to SSRS. The minimum ponded pressure head used in the datasets reported here was 0.5 cm, so that is the lower limit of ponded head that this analysis can identify but if there is a significant threshold pressure head it may be smaller.…”
Section: Measurement Methods Impactsmentioning
confidence: 76%
“…Work in unburned conditions also shows sensitivity to ponded head. For example, Morbidelli et al (2017) compared TI, FHP, and SSRS K fs estimates and found that TI and SSRS methods produced similar mean K fs , but TI K fs was more variable, whereas FHP produced K fs estimates that were larger on average by nearly a factor of 5 compared to SSRS. K fs studies in burned conditions suggested larger positive heads applied at the surface boundary condition by FHP and CHP may induce infiltration into water repellent porous media by exceeding the water entry value (Nyman et al, 2010;Ebel et al, 2012) or activating preferential flow paths (Nyman et al, 2014;Langhans et al, 2016) that may not be accessed by TI and SSRS.…”
Section: Discussionmentioning
confidence: 99%
“…Estimation of K s at the point scale requires a solution to an inverse problem that involves measurements of other quantities (e.g., soil moisture content and soil-water suction) and use of an infiltration model (e.g., Corradini et al, 1997;Green & Ampt, 1911;Parlange et al, 1982;Philip, 1957;Richards, 1931). Apart from problems noted with such point estimates from measuring instruments (Boers et al, 1992;Cook & Broeren, 1994;Jabro & Evans, 2006;Morbidelli et al, 2017;Verbist et al, 2013), a very large number of these measurements are needed to assess the nature of spatial variability at the field scale because of the high degree of spatial variability found in the infiltration properties of natural soils (Russo & Bresler, 1981). Field studies (Loague & Gander, 1990;Morbidelli et al, 2017;Nielsen et al, 1973;Sharma et al, 1987) have shown that even seemingly uniform areas manifest large variations in K s .…”
Section: Introductionmentioning
confidence: 99%
“…Apart from problems noted with such point estimates from measuring instruments (Boers et al, 1992;Cook & Broeren, 1994;Jabro & Evans, 2006;Morbidelli et al, 2017;Verbist et al, 2013), a very large number of these measurements are needed to assess the nature of spatial variability at the field scale because of the high degree of spatial variability found in the infiltration properties of natural soils (Russo & Bresler, 1981). Field studies (Loague & Gander, 1990;Morbidelli et al, 2017;Nielsen et al, 1973;Sharma et al, 1987) have shown that even seemingly uniform areas manifest large variations in K s . Several studies, such as Dagan and Bresler (1983), have stated that K s exhibits the maximum spatial variability among infiltration parameters and can be represented using a lognormal random field.…”
Section: Introductionmentioning
confidence: 99%
“…Saturated hydraulic conductivity, K s , of the surface soil layer is the most important soil parameter that influences rainfall partition into infiltration and surface runoff (Assouline & Mualem, , ), and it can be determined with infiltrometer runs. However, the K s data collected with these techniques could be thought to be unusable for hydrological studies since several investigations have shown that the K s results were much higher than those obtained by other methods, or they were incompatible with any rainfall excess even if surface runoff was measured (Bagarello, Di Stefano, Iovino, & Sgroi, ; Cerdà, , ; Morbidelli et al, ; van de Giesen, Stomph, & De Ridder, ; Williams & Bonell, ). This inconsistency can depend on different factors such as blocking of some large pores by massive air inclusion during natural events or crust formation and associated particle sorting decreasing overall permeability during the storm (Van de Giesen et al, ) but not, or not at the same rate, during the infiltration run.…”
Section: Introductionmentioning
confidence: 99%